The extraction mechanism of heavy metals by natural materials; Modern Technique and Technologies. MTT 2002 - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna (2002, 2002)
The process of heavy metals cations extraction from aqueous solutions on source calcium-magnesium minerals of carbonate and silicate rocks flows under the ion exchange schema, and the ion exchange is a tracked precipitation of hydroxides of metals on pretreated samples of carbonate rocks.